2007
DOI: 10.1111/j.1365-294x.2007.03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the number of whales entering trade using DNA profiling and capture‐recapture analysis of market products

Abstract: Surveys of commercial markets combined with molecular taxonomy (i.e. molecular monitoring) provide a means to detect products from illegal, unregulated and/or unreported (IUU) exploitation, including the sale of fisheries bycatch and wild meat (bushmeat). Capture-recapture analyses of market products using DNA profiling have the potential to estimate the total number of individuals entering the market. However, these analyses are not directly analogous to those of living individuals because a 'market individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…Some of these have already been utilized to reveal discrepancies in reported marine mammal bycatch, to determine the magnitude of trade and to develop kits that rapidly identify marine mammal species in situ in Asian markets (Baker et al, 2006(Baker et al, , 2007Lukoschek et al, 2009;Lo et al, 2013). These tools, designed specifically for non-specialists, will allow quantitative data collection both on type and volume of marine mammal parts in Asian markets.…”
Section: Lessons and Conclusion From Terrestrial Wildlife Trade Studiesmentioning
confidence: 99%
“…Some of these have already been utilized to reveal discrepancies in reported marine mammal bycatch, to determine the magnitude of trade and to develop kits that rapidly identify marine mammal species in situ in Asian markets (Baker et al, 2006(Baker et al, , 2007Lukoschek et al, 2009;Lo et al, 2013). These tools, designed specifically for non-specialists, will allow quantitative data collection both on type and volume of marine mammal parts in Asian markets.…”
Section: Lessons and Conclusion From Terrestrial Wildlife Trade Studiesmentioning
confidence: 99%
“…Actually, several studies reported that there was a high number of illegal, unreported or unregulated catches for this stock (Baker et al 2006(Baker et al , 2007Lukoschek et al 2009). Also, the default value of R max was used to estimate PBR for minke whales in this area because the data on R max were insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the status of J stock minke whales, abundance (Kitakado et al 2010) and mortality (Baker et al 2007;Lukoschek et al 2009) data of this stock were used. Also, to investigatethe trend in abundance of minke whales in Korean waters, abundance data of minke whales in the East Sea of Korea from 2000 to 2008 were used .…”
Section: Methodsmentioning
confidence: 99%
“…For example, Tinch and Phang (2009) report that prices in 2006 in Japan were around US$16 per kg, compared to prices of up to US$37/kg in South Korea for confiscated fresh whale meat. Illegal hunting is potentially also a major source of meat based on verbal comments by our interviewees and previous studies on whale meat market in South Korea (Dalebout et al 2002;Baker et al 2006Baker et al , 2007. Indeed, one interviewee reported that many restaurant owners would actually only buy token amounts of legal by-catch to cover up their primary illegal source and another confessed in a follow-up chat in 2010 that auction prices of by-catch are highly dependent on 'the illegal supply.'…”
Section: By Chance or By Design?mentioning
confidence: 99%